Mister Exam

x^2+2y^2 canonical form

The teacher will be very surprised to see your correct solution 😉

v

The graph:

x: [, ]
y: [, ]
z: [, ]

Quality:

 (Number of points on the axis)

Plot type:

The solution

You have entered [src]
 2      2    
x  + 2*y  = 0
x2+2y2=0x^{2} + 2 y^{2} = 0
x^2 + 2*y^2 = 0
Detail solution
Given line equation of 2-order:
x2+2y2=0x^{2} + 2 y^{2} = 0
This equation looks like:
a11x2+2a12xy+2a13x+a22y2+2a23y+a33=0a_{11} x^{2} + 2 a_{12} x y + 2 a_{13} x + a_{22} y^{2} + 2 a_{23} y + a_{33} = 0
where
a11=1a_{11} = 1
a12=0a_{12} = 0
a13=0a_{13} = 0
a22=2a_{22} = 2
a23=0a_{23} = 0
a33=0a_{33} = 0
To calculate the determinant
Δ=a11a12a12a22\Delta = \left|\begin{matrix}a_{11} & a_{12}\\a_{12} & a_{22}\end{matrix}\right|
or, substitute
Δ=1002\Delta = \left|\begin{matrix}1 & 0\\0 & 2\end{matrix}\right|
Δ=2\Delta = 2
Because
Δ\Delta
is not equal to 0, then
find the center of the canonical coordinate system. To do it, solve the system of equations
a11x0+a12y0+a13=0a_{11} x_{0} + a_{12} y_{0} + a_{13} = 0
a12x0+a22y0+a23=0a_{12} x_{0} + a_{22} y_{0} + a_{23} = 0
substitute coefficients
x0=0x_{0} = 0
2y0=02 y_{0} = 0
then
x0=0x_{0} = 0
y0=0y_{0} = 0
Thus, we have the equation in the coordinate system O'x'y'
a33+a11x2+2a12xy+a22y2=0a'_{33} + a_{11} x'^{2} + 2 a_{12} x' y' + a_{22} y'^{2} = 0
where
a33=a13x0+a23y0+a33a'_{33} = a_{13} x_{0} + a_{23} y_{0} + a_{33}
or
a33=0a'_{33} = 0
a33=0a'_{33} = 0
then equation turns into
x2+2y2=0x'^{2} + 2 y'^{2} = 0
Given equation is degenerate ellipse
x~212+y~2(22)2=0\frac{\tilde x^{2}}{1^{2}} + \frac{\tilde y^{2}}{\left(\frac{\sqrt{2}}{2}\right)^{2}} = 0
- reduced to canonical form
The center of canonical coordinate system at point O
(0, 0)

Basis of the canonical coordinate system
e1=(1, 0)\vec e_1 = \left( 1, \ 0\right)
e2=(0, 1)\vec e_2 = \left( 0, \ 1\right)
Invariants method
Given line equation of 2-order:
x2+2y2=0x^{2} + 2 y^{2} = 0
This equation looks like:
a11x2+2a12xy+2a13x+a22y2+2a23y+a33=0a_{11} x^{2} + 2 a_{12} x y + 2 a_{13} x + a_{22} y^{2} + 2 a_{23} y + a_{33} = 0
where
a11=1a_{11} = 1
a12=0a_{12} = 0
a13=0a_{13} = 0
a22=2a_{22} = 2
a23=0a_{23} = 0
a33=0a_{33} = 0
The invariants of the equation when converting coordinates are determinants:
I1=a11+a22I_{1} = a_{11} + a_{22}
     |a11  a12|
I2 = |        |
     |a12  a22|

I3=a11a12a13a12a22a23a13a23a33I_{3} = \left|\begin{matrix}a_{11} & a_{12} & a_{13}\\a_{12} & a_{22} & a_{23}\\a_{13} & a_{23} & a_{33}\end{matrix}\right|
I(λ)=a11λa12a12a22λI{\left(\lambda \right)} = \left|\begin{matrix}a_{11} - \lambda & a_{12}\\a_{12} & a_{22} - \lambda\end{matrix}\right|
     |a11  a13|   |a22  a23|
K2 = |        | + |        |
     |a13  a33|   |a23  a33|

substitute coefficients
I1=3I_{1} = 3
     |1  0|
I2 = |    |
     |0  2|

I3=100020000I_{3} = \left|\begin{matrix}1 & 0 & 0\\0 & 2 & 0\\0 & 0 & 0\end{matrix}\right|
I(λ)=1λ002λI{\left(\lambda \right)} = \left|\begin{matrix}1 - \lambda & 0\\0 & 2 - \lambda\end{matrix}\right|
     |1  0|   |2  0|
K2 = |    | + |    |
     |0  0|   |0  0|

I1=3I_{1} = 3
I2=2I_{2} = 2
I3=0I_{3} = 0
I(λ)=λ23λ+2I{\left(\lambda \right)} = \lambda^{2} - 3 \lambda + 2
K2=0K_{2} = 0
Because
I3=0I2>0I_{3} = 0 \wedge I_{2} > 0
then by line type:
this equation is of type : degenerate ellipse
Make the characteristic equation for the line:
I1λ+I2+λ2=0- I_{1} \lambda + I_{2} + \lambda^{2} = 0
or
λ23λ+2=0\lambda^{2} - 3 \lambda + 2 = 0
λ1=2\lambda_{1} = 2
λ2=1\lambda_{2} = 1
then the canonical form of the equation will be
x~2λ1+y~2λ2+I3I2=0\tilde x^{2} \lambda_{1} + \tilde y^{2} \lambda_{2} + \frac{I_{3}}{I_{2}} = 0
or
2x~2+y~2=02 \tilde x^{2} + \tilde y^{2} = 0
x~2(22)2+y~212=0\frac{\tilde x^{2}}{\left(\frac{\sqrt{2}}{2}\right)^{2}} + \frac{\tilde y^{2}}{1^{2}} = 0
- reduced to canonical form